2019 8th International Conference on Affective Computing and Intelligent Interaction (ACII) 2019
DOI: 10.1109/acii.2019.8925453
|View full text |Cite
|
Sign up to set email alerts
|

Nose Heat: Exploring Stress-induced Nasal Thermal Variability through Mobile Thermal Imaging

Abstract: Automatically monitoring and quantifying stressinduced thermal dynamic information in real-world settings is an extremely important but challenging problem. In this paper, we explore whether we can use mobile thermal imaging to measure the rich physiological cues of mental stress that can be deduced from a person's nose temperature. To answer this question we build i) a framework for monitoring nasal thermal variable patterns continuously and ii) a novel set of thermal variability metrics to capture a richness… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
29
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(29 citation statements)
references
References 24 publications
0
29
0
Order By: Relevance
“…Nose Temperature: The human internal temperature correlates with physical and psychological states [33].The reaction to stimuli increases or decreases blood ow which leads to variation in skin temperature. The variability in skin temperature is often measured with thermal imaging [34].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Nose Temperature: The human internal temperature correlates with physical and psychological states [33].The reaction to stimuli increases or decreases blood ow which leads to variation in skin temperature. The variability in skin temperature is often measured with thermal imaging [34].…”
Section: Introductionmentioning
confidence: 99%
“…Among other facial regions, the nose tip is regarded as providing the most consistent indications of stress. Once stressful conditions apply, the nasal temperature decreases [33].…”
Section: Introductionmentioning
confidence: 99%
“…To overcome these limitations, infrared thermography (IRT) has recently been used to measure the breathing characteristics of cattle [ 5 , 6 ]. In fact, IRT has been used not only to measure breathing but also in various fields such as stress assessment by eye temperature [ 7 , 8 , 9 ] or nose temperature [ 10 ]. However, the previous methods have utilized it in a limited way.…”
Section: Introductionmentioning
confidence: 99%
“…the temperature of a particular regions of interest, such as the eyes, ears or tails. Moreover, it has already been shown that the equipment needed to collect such non-invasive data can be mobilized, increasing the feasibility to employ such equipment within a larger industrial setting ( 40 , 50 , 76 ). More and more studies demonstrate the applications of automated systems within a farm setting, highlighting the potential of this field, ranging from surveying pig enclosure usage to identifying heat stress ( 77 ) to infrared thermography to track cattle health ( 76 ).…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has already been shown that the equipment needed to collect such non-invasive data can be mobilized, increasing the feasibility to employ such equipment within a larger industrial setting ( 40 , 50 , 76 ). More and more studies demonstrate the applications of automated systems within a farm setting, highlighting the potential of this field, ranging from surveying pig enclosure usage to identifying heat stress ( 77 ) to infrared thermography to track cattle health ( 76 ). Human affective research is only just starting to understand the importance of multimodal approaches, and this knowledge should be used to develop models for non-human animals, too.…”
Section: Introductionmentioning
confidence: 99%